Media freedom and responsibility - Rajapakshe, Wijeyadasa ([Nugegoda] : W. Rajapakshe, 2000)
An overview of the media case laws and practice, their concepts, ethics and traditions in Sri Lanka.
Book is a photocopy version.
Keywords: Mass media -- Law and legislation -- Sri Lanka; Press law -- Sri Lanka; Freedom of the press -- Sri Lanka